Family Resilience of Lottery Gamblers in Kedungrejo Village, Tunjungan District, Blora Regency - Lesmana, Bondan; DWP, Sucihatiningsih; Handoyo, Eko (Universitas Negeri Semarang, 2023)
Teachers in schools have carried out social studies learning, but it will be more optimal if they get support from the family. The low human resources and economy caused family members to play lottery gambling. This study aims to determine the causes of lottery gambling in coffee shops and their impact on family resilience. This research uses qualitative methods. Data collection techniques are observation, interviews and documentation. The results of this study show that lottery gambling in Bokerto Hamlet coffee shops is caused by the economic motives and political relationships between coffee shop owners and government officials. In addition, socialization factors from deviant sub-cultures and the social and cultural environment also support gambling activities. The existence of lottery gambling in coffee disrupting the strength of families consisting of lottery gamblers. Families who are disturbed by their resilience fail to meet the mental-spiritual and psychological components. Childrens of lottery gamblers who study at junior and senior high school levels have not been able to force their parents to stop playing the lottery, while they who have grown up are permissive. This research is expected to contribute to thinking that every parent has an important role to create family resilience.